Does basic medical insurance promote public health? Evidence from China family panel study - Liao, Fuchong; Hu, Wenxiu; Zhang, Chun (Frontiers in Public Health, 2023)
Background: To promote common prosperity, China government has devoted much financial resources to the basic medical insurance system, it is of great significance to improve the health level of the insured groups to prevent them from returning to poverty due to illness. Whether or not the basic medical insurance can improve health status is an important policy issue after China has win the absolute poverty alleviation movement. Methods: Based on the data of China Family Panel Studies (CFPS) from 2010 to 2020, this paper constructs a strong balanced panel data with two levels information, which including variables from family level and personal level. This paper uses the panel data fixed effect model and propensity score matching model to analysis. Results: This paper finds that after controlling the family and personal confounding variables, the basic medical insurance has positive effect towards health status. With propensity score matching model, this paper finds that there is causality between basic medical insurance and public health. Conclusion: Basic medical insurance has a significant health effect, that is, basic medical insurance has a significant positive impact on individual self-rated health. Participating in basic medical insurance can significantly improve the ability of families to face risk shocks, promote the accumulation of health capital in families, promote the diversification of livelihood strategies, and effectively prevent the occurrence of returning to poverty due to illness